Exploration of value arguments in applied linguistics research articles. Issue 59 (September 2022) - Azizi, Mohammad; Abdi, Jalil; Gholami, Javad
Abstract: The marketization of all public spheres, including the academic community, and the growing competitiveness to publish papers have led to the increasing importance of promotion in Research Articles (RAs). One realization of promotion in the introduction sections of RAs is the use of value arguments, which are the arguments made to accentuate the importance (value) of the research. The present study explores value arguments in the introduction sections of Applied Linguistics (AL) RAs. To this end, the introduction sections of 30 RAs from several AL journals were selected as the corpus of the study. The forms and functions of value arguments were analyzed using Carter's (2016) framework. The results revealed that writers in the discipline of AL mainly use implicit value arguments – a type of value arguments that tacitly underscore the importance of research – and that different functions have disparate rates of occurrence and tend to appear in relatively predictable places in the introduction sections. It is hoped that the findings of this study could raise awareness about promotion through such arguments in scholarly writing practices.